Value generating creative elements of brand and design in sustainable fashion context : Cases of Halla x Halla & Globe Hope - Koivula, Paiju (fi=Turun yliopisto|en=University of Turku|, 2018)
Due to the current changes in the business environment, sustainability as subject of research has been given more attention. However, there is still lack of research on the topic, and the existing sustainability literature regularly emphasizes the technical side of sustainability, such as supply chain management, life cycle management or greener production systems. The creative side of sustainable business is a less-studied field within the sustainability research, which is why it offered an interesting and current topic that requires further exploration. Therefore, the purpose of this study was to analyze value generating, creative elements of brand and design in sustainable fashion context. The general purpose was divided into three research questions which sought answers to how different brand and design elements manifest themselves in sustainable fashion and which are the main challenges in building an appealing sustainable fashion brand in online context. The research questions were approached by using qualitative content analysis as the method and by conducting a case study. Two Finnish sustainable fashion brands were selected for the empirical analysis, whose tangible and intangible brand elements and product designs were assessed. The data was collected from the two brands’ online channels, and also content from other than the companies’ own online platforms, such as fashion blogs, was collected. The empirical analysis suggested that the sustainable fashion brand which concentrated less on sustainability seemed more creative in terms of design and brand elements, and perhaps even more successful. Correspondingly, in the light of this research, the challenges that sustainable fashion brands tend to face are concerned with dull brand image, unsatisfactory product design which is perceived as plain yet high-cost, and issues with how to communicate about sustainability. The theoretical background and empirical analysis implied that to create an appealing sustainable fashion brand in the eyes of non-green consumers, it is paramount that the clothes fulfil the core value generating elements of fashion clothing first and meet the aesthetic standards of the industry, after which the sustainability aspect must be regarded more as an added value. Another fundamental aspect that arose in creating an appealing sustainable fashion brand in online environment is visuality; when products are chosen online solely based on the pictures, the importance of the products’ visual appearance is even greater. Visuality and the use of images are vital parts of electronic commerce, and in the clothing business the product images are particularly essential.